KERJA SAMA INTERNASIONAL DALAM KERANGKA PERTUKARAN TEKNOLOGI DAN INFORMASI BISNIS UNTUK PRODUK PERALATAN LISTRIK DI WENZHOU, TIONGKOK - Pelawi, Zulfadli; Alam, Hermansyah; Parinduri, Luthfi (Jurnal Masyarakat Indonesia (Jumas), 2025)
Community service plays a vital role in empowering communities and driving economic development, especially in technology and business. In the electrical equipment industry, international cooperation is key to enhancing global competitiveness through the exchange of technology and business information. This activity, held in September 2024 in collaboration with partners in Wenzhou, China, aimed to introduce advanced technologies and business practices to Indonesia’s electrical equipment sector. The program included technical training, discussions, and technology demonstrations, focusing on business management, marketing, and supply chain skills. It also sought to strengthen ties between Indonesian industry players and their counterparts in China. Participants gained valuable knowledge on cutting-edge technologies, expanded their international business networks, and improved their competitiveness in global markets. The positive impact of this initiative is expected to significantly contribute to the growth of Indonesia’s electrical equipment industry. It is recommended to continue expanding international cooperation and offering ongoing training to further enhance industry competitiveness.